Intimate Outsiders - Roberts, Mary.
1 online resource (243 pages)
Keywords: Comparative study of 19th-century representations of Ottoman harems that considers both the tradition of British paintings and writings about harems as well as the perspectives of Ottoman women who commissioned their own harem portraits.